HUBUNGAN MOBILISASI DINI PADA IBU POST OPERASI SECTIO CAESAREA DENGAN PENGELUARAN LOCHEA RUBRA DI RSUD Dr. M. ASHARI KABUPATEN PEMALANG - Purwanti, Etna; Happinasari, Ossie; Fajarsari, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Sectio Caesarea is the baby spending from an intact uterus through abdominal surgery. After the sectio caesarea measure should be done early mobilization. The early mobilization was the prudence as soon as possible ato guide the patients out from their bed and to walked, the early mobilization can be used to expedite the lochea rubra spending. This research want to Knowing the relationship of early mobiliation on post sectio caesarea women with lochea rubra spending in Dr. Ashari Hospital Pemalang Regency. The method of research used in this study is observasional analytical with cohort approach. The population in this study were all of the mother who gave birth sectio caesarea method in April. The samples technic used accidental sampling The samples used were 30 people. The data analysis were univariate analysis was used the frequency distribution and bivariate analysis was used chi square test. The statistical test result majority of mothers do early mobilization post SC ≤ 24 hours a total of 26 respondents (86.7%). The majority of mothers post SC issued lochea rubra occurred during ≤ 4 days total of 26 respondents (86.7%). There is a related between early mobilization on post sectio caesarea women with lochea rubra spending in Dr. M. Ashari Hospital Pemalang Regency in 2013 it’s proven from p value = 0.000 (p <0,05). Conclusion: There is a related between early mobilization on post sectio Caesarea women with lochea rubra in Dr. M. Ashari Hospital Pemalang Regency in 2013. Keywords: Early mobilization, Post SC, Lochea rubra